Pengaruh Penggunaan Dompet Digital (E-Wallet) terhadap Perilaku Konsumtif Perspektif Islam pada Generasi Milenial Daerah Istimewa Yogyakarta - Alfira Dwi Astuti; Ani Faujiah (Islamic Economics Study Program, Faculty of Sharia and Islamic Economics, Universitas Annuqayah, 2023)
In the current era, humans are facing technological advances as a result of globalization. This information and communication technology pushes to go global and create new style changes in society, especially in terms of payments. The existence of the cashless phenomenon in Indonesia The phenomenon of the existence of a cashless society has led to the emergence of many electronic wallets in Indonesia. With the ease with which you can make new style changes because there are promos, practicality, and convenience as a result of this phenomenon, the community, especially the DIY area, will experience an increase in digital wallets in 2022 accompanied by Millennials who contribute online shopping and transact using QRIS. This study aims to determine how much influence digital wallets (e-wallets) have on Islamic consumptive behavior in the Millennial Generation of the Special Region of Yogyakarta. This type of research is quantitative research with quantitative descriptive analysis with purposive sampling. The samples taken were 100 respondents. The data collection method is distributed using Google Forms. The results of this study indicate that there is a relationship between the two variables. And it means that Millennials are very consumptive when using QRIS because there are promos, convenience, practicality and it can be interpreted that DIY millennials do not apply Islamic consumption ethics because they buy not according to their needs but according to their wishes.